1979
DOI: 10.1017/s0007485300017934
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering and spring emergence of Heliothis armigera (Hübner) (Lepi–doptera: Noctuidae) in the Namoi Valley, New South Wales

Abstract: The overwintering of Heliothis armigera (Hb.) was studied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 8 publications
2
74
1
1
Order By: Relevance
“…Their results corroborate our findings that higher humidity levels lengthen the larval period of A. malefida. The occurrence of prepupal diapause in A. malefida (BENTANCOURT & SCATONI 2006) has already been reported for some noctuid species in other genera, such as in Xestia c-nigrum (Linnaeus, 1758) (HONÌK 1979, OKU 1984, Helicoverpa armigera (Hübner, [1809]) (WILSON et al 1979, QURESHI et al 2000, FENG et al 2010, and S. nonagrioides (FANTINOU et al 1996, GADENNE et al 1997, EIZAGUIRRE et al 2008. However, larval and pupal diapause were not expected to occur in A. malefida under the rearing conditions of our experiment (25 ± 1°C, 70 ± 10% RH and 14 hours photoperiod).…”
Section: Larval Stagementioning
confidence: 80%
“…Their results corroborate our findings that higher humidity levels lengthen the larval period of A. malefida. The occurrence of prepupal diapause in A. malefida (BENTANCOURT & SCATONI 2006) has already been reported for some noctuid species in other genera, such as in Xestia c-nigrum (Linnaeus, 1758) (HONÌK 1979, OKU 1984, Helicoverpa armigera (Hübner, [1809]) (WILSON et al 1979, QURESHI et al 2000, FENG et al 2010, and S. nonagrioides (FANTINOU et al 1996, GADENNE et al 1997, EIZAGUIRRE et al 2008. However, larval and pupal diapause were not expected to occur in A. malefida under the rearing conditions of our experiment (25 ± 1°C, 70 ± 10% RH and 14 hours photoperiod).…”
Section: Larval Stagementioning
confidence: 80%
“…A visible characteristic of arrested development in diapausing pupae was the prolonged presence of pigmented ocelli (Phillips & Newsom 1966). Wilson et al (1979), in Australia, found that time taken to terminate diapause varied considerably between individual pupae.…”
Section: Heliothis Armiger Confertusmentioning
confidence: 99%
“…Helicoverpa armigera enters into facultative diapause at the pupal stage (Fitt, 1989). In the field, subtropical populations of the species are capable of overwintering in a state of pupal diapause in Africa and Australia (Roome, 1979;Wilson et al, 1979). In Australia, a HEAPS model has been developed based on the local field information and is being used to predict the number of overwintering pupae of Helicoverpa moths (Dillon, 1998).…”
Section: Introductionmentioning
confidence: 99%